Effective Programs to Increase Physical Activity Participation and Physical Fitness Levels: A Literature Review - Wicahyani, Sri; Setijono, Hari; Wibowo, Sapto; Nur Muhammad, Heryanto; Hidayat, Taufiq; Prasetyo, Agung; Williyanto, Septian (Proceeding of International Joint Conference on UNESA, 2025)
The purpose of this study was to analyze the effective programs for increasing physical activity participation and physical fitness levels. The research method used is a systematic review of articles with the Scopus database. Researchers used the Spider framework whose inclusion criteria were: sample: students or youth; phenomenon of interest focused on programs for students or youth, about programs to increase sports participation and physical activity; survey or experimental research design, evaluation: effectiveness of programs to promote sports participation and physical activity; type of research is basic research. The research results state that the research in the selected articles was conducted with the ultimate goal of improving health and well-being through increasing physical activity. Research primarily focused on increasing, measuring, or understanding physical activity. Other research attempted to identify factors that influence the level of participation or success of physical activity programs. Program recommendations include increasing MVPA among middle school students during indoor classes, designing and implementing not only activities focused strictly on PA but also activities at home, subsequent physical activity interventions, and implementing school policies that encourage walking to and from school at specific distances. Campus programs such as sports clubs, summer programs, and spontaneous sporting events can be a way to increase physical activity participation and fitness in children and adolescents. Sports clubs offer opportunities to pursue specific interests in a supportive and fun atmosphere. Spontaneous sporting events can be designed to be inclusive and accessible to a variety of fitness levels, thereby attracting broader participation.